Assessment of moisture content measurement methods of dried food products in small-scale operations in developing countries: A review. (June 2019) - Vera Zambrano, Marina; Dutta, Baishali; Mercer, Donald G.; MacLean, Heather L.; Touchie, Marianne F.
Abstract: Background: Moisture-related microbial growth is a key factor contributing to food spoilage in developing countries. Dehydration or drying of food reduces the moisture content supporting this microbial growth, thereby addressing this problem. Hence the moisture content of food materials is a key factor influencing the quality of storage thereby reducing post-harvest loss and is thus very important for the farmers. Scope and approach: Current moisture measurement techniques (both destructive and non-destructive) available do not take into account the inherent difficulties in the context of developing countries including the relatively high instrumentation cost, unreliable power supply, specificity of the measurement method to food type, and training and maintenance requirements, among others. This paper includes a review of the existing moisture content measurement methods followed by an evaluation of their applicability for this proposed application in developing countries. Key Findings and Conclusions : A few recently developed instruments show promise but there is little research on how small-scale farms and co-operatives in developing countries can achieve a safe standard for their dried foods. Of these, two potential methods, equilibrium relative humidity and infrared imaging, were identified as promising techniques, but further research and development would be needed to make them suitable for use in small-scale operations in developing countries. Highlights: Study presents review of common moisture content measurement methods. Current techniques do not consider inherent difficulties in developing countries. Analysis conducted to determine feasible methods for developing country applications. Equilibrium relative humidity and infrared imaging identified as promising techniques.